Does the Exchange Regime Matter for inflation and Growth?. (Economic Issues; Economic Issues, 1996)
Although the theoretical relationships are ambiguous, evidence suggestsa strong link between the choice of the exchange rate regime and economicperformance. The paper argues that adopting a pegged exchange rate canlead to lower inflation, but also to slower growth in productivity. Itfinds that on average per capita GDP growth was slightly faster underfloating regimes than under pegged exchange regimes.